PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL â€œECLIPSE AMMU PEâ€ TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Cornelia Amanda Naitili; Kristina E. Noya Nahak (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
This study aims to determine the impact of using local wisdom-based learning media "Eclipse Ammu Pe" on students' interest and learning outcomes in science subjects at the primary school level. The research method used was a pretest-posttest control group experimental design involving students of class V of SDN Fatke. Learning outcome data were measured using pretest and posttest written tests. In addition, students' interest in learning was also assessed through observation and questionnaire. The results of data analysis showed that the experimental group using local wisdom-based learning media experienced a significant increase in learning outcomes and also showed a higher increase in learning interest compared to the control group. Statistical tests showed a low significance value (0.000) for the effect of learning media on students' learning outcomes and interest in learning. These results indicate that the use of local wisdom-based learning media "Eclipse Ammu Pe" has a positive impact on students' interest in science and learning outcomes. The implications include the potential for developing more contextualized and interesting learning strategies as well as the application of local wisdom-based learning media in science education. However, this study has limitations in terms of generalizability and consideration of other factors that may influence students' interest and learning outcomes. Further research is needed to gain a comprehensive understanding of the study.